Pertumbuhan Tanaman Padi Payo Kerinci Menggunakan System of Rice Intensification (SRI) - Andesmora, Evan V; Aprianto, Riko; Novallyan, Devie; Aprisi, Fella (Universitas Pattimura, 2023)
Payo Kerinci Rice is one of the germplasms whose existence must be maintained. This rice is one of the local rice varieties, which is quite rare. Payo rice has a relatively high economic value compared to other rice varieties. This is due to the unique and fragrant taste of the rice, so it is very popular with the public. Increased growth is one of the initial stages in projecting success in rice plant productivity. The System of Rice Intensification (SRI) method is hoped to provide an alternative for farmers in cultivating Payo Kerinci rice. The research method was carried out experimentally using divided plots by comparing the SRI and Conventional methods. The growth parameters observed were plant fresh weight, plant dry weight, number of tillers, plant height, and root length. The research results show that the SRI method provides efficiency in the need for seeds in Payo Kerinci Rice cultivation. The Payo Kerinci rice plants using the SRI single seedling method grew more than the conventional method for all observed variables.